Mechanism design and human-machine coupling analysis for a lumbar rehabilitation robot - Tian, Yuan; Chen, Fengping; Zhao, Zixu; Jiang, Dawei; Ji, Wenjing; Dai, Jiasheng (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionSuperman Exercise is highly recommended by healthcare professionals for patients with low back pain. However, performing this treatment can be challenging due to patients’ difficulty in maintaining the training maneuvers and the lack of standardization in these maneuvers.Methods and proceduresA low back rehabilitation robot, designed based on swallow movement rehabilitation training, was fully modeled for patients with low back motor dysfunction. The robot underwent kinematic analysis, including forward and inverse solutions, as well as kinetic analysis to verify its accuracy. By studying human waist mobility and muscle force, a human-machine coupling model was developed to determine the range of human waist joint angles and muscle force size. This was achieved by importing three-dimensional motion capture data into the OpenSim human motion analysis environment and comparing it with the human body’s natural lumbar rehabilitation movements. Additionally, comparisons were made with the human body during lumbar rehabilitation training maneuvers.ConclusionThe rehabilitation robot is well-designed to meet patients’ rehabilitation training needs and uncover the rehabilitation patterns of the human waist. This study serves as a reference for future parameter optimization and control system design.